Avaliação das alterações estruturais associadas ao glaucoma de pressão normal em pacientes com esclerose sistêmica. - Tito, Cecilia Victoria Agapito [UNIFESP] (2019)
Introduction: Vascular dysfunction, characterized by vascular hyperreactivity and endothelial activation, represents a central and early event in systemic sclerosis (SSc). A number of evidences suggested that vascular abnormalities are involved in the pathogenesis of normal-tension glaucoma (NTG), as ocular vasospasm may induce optic nerve head damage. Objectives: To investigate the presence of structural markers of NTG damage in SSc. In addition, we evaluated the correlations between ophthalmologic evaluation and clinical, capillaroscopic parameters and measures of digital blood flow using laser Doppler imaging in SSc patients. Material and Methods: In this cross-sectional study, 40 patients with SSc (2013 ACR/EULAR classification criteria) and 23 age- and sex-matched controls were included. All participants underwent complete ophthalmological examination, including visual acuity, intraocular pressure (IOP), slit-lamp biomicroscopy, gonioscopy and visual field examination. Mean and sectoral peripapillary retinal nerve fiber (RNFL) thickness, sectoral and global of macular RNFL, ganglion cell layer (GCL)+ (GCL+inner plexiform layer [IPL]), GCL++ (RNFL+GCL+IPL) thickness and optic disc morphology were measured using swept-source optical coherence tomography (SS-OCT, DRI OCT; Topcon, Tokyo, Japan). Furthermore, the evaluation of morphology and function of the microcirculation were performed using nailfold capillaroscopy (NFC) and the measurement of the digital blood flow of the second to fifth fingers of the non-dominant hand by means of Laser Doppler imaging (LDI). Results: A total of 46 eyes of normal subjects, and 80 eyes of SSc patients were evaluated. The mean IOP in SSc patients was of 14.65 ± 2.98 mmHg and of 14.74 ± 2.64 mmHg in controls (p=0.58). The mean RNFL was of 106.23 ±11.35 μm in SSc patients and of 108.96 ± 13.74 μm in controls (p=0.29). SSc patients showed a thinner RNFL in the temporal and nasal quadrants compared with the controls (temporal RNFL: 72.58 ± 15.64 μm versus 83.41 ± 37.10 μm, p=0.005; nasal RNFL: 82.44 ± 13.16 μm versus 87.76 ± 15.73 μm, p = 0.045, respectively). The inner temporal macular thickness measurement were significantly lower (p= 0.045) in SSc eyes than in controls. The optic disc area was also significantly smaller in SSc patients compared to controls (p=0.03). In SSc patients the time of Raynaud phenomenon (RP) showed an inverse correlation with the mean RNFL (p=0.012). The disease duration had an inverse correlation with the mean RNFL (p=0.003) and the superior RNFL (p=0.026). The macular retinal nerve fiber layer shower and inverse correlation with the disease duration in the fovea (p=0.005), outer superior (p= 0,037), outer nasal (p = 0.001), inner superior (p= 0.015), inner inferior (p=0,002), inner temporal (p= 0,039),and inner nasal (p<0.001) segments, as well as with the mean macular thickness (p= 0,003). Similar correlations were also observed with the duration of RP. In the sector analysis of macular ganglion cells, there were a significant inverse correlation between the disease and RP duration and the total and superior GCL+ thickness as well as superior GCL++ thickness. LDI did not showed correlation with OCT parameters. Interestingly, there was an inverse correlation between the avascular score in NFC and the vertical cup/disco ratio (p=0.041), the cup volume (p=0.018), and an inverse correlation with the macular thickness of the fovea, the lower inner and the temporal inner quadrants (p = 0.029, p= 0.039, p = 0.047, respectively). CONCLUSION: Considering the significant decrease of the RNFL thickness in temporal e nasal quadrants and of the macular RNFL in patients with SSc compared with the control group, as well as the decrease in the optic disc area, a decreased blood flow decrease associated with an ocular vasospasm may result in ganglion cell damage in SSc patients. These abnormalities might be associated with an increased risk for developing glaucomatous damage in patients with SSc. Further prospective studies with higher number of patients are necessary to better understand the structural damage and glaucomatous abnormalities in SSc.